ANTI -ARTHRITIC POTENTIAL OF HELIANTHUS ANNUUS IN LABORATORY ANIMALS - A SURALKAR, ANUPAMA; S, JADHAV; NA, GUPTA; CT, BHOITE (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The present study was carried out to investigate the anti-arthritic potential of ethanolic extract of Helianthus annuus leaves (HA). Methods: The effect of HA was evaluated for chronic inflammation by complete Freud's adjuvant (CFA) induced arthritis in rats. Results: The paw edema was measured along with biochemical, hematological, histopathological, radiographic parameters, and ulcerogenic potential. In this study, pre-treatment with HA significantly decreased paw volume, arthritic index, spleen and thymus weight, ulcerogenic index; and inhibited histopathological changes in joint cavity and inhibited destruction of the knee joints induced by CFA in radiographic examination. Treatment of HA also restored significantly the hematological parameters such as hemoglobin level, total red blood cell, total white blood cell, and erythrocytsedimentation rate along with antioxidant parameters such as superoxide dismutase, catalase glutathione, and lipid peroxide. The serum marker of arthritis such as C-reactive protein (CRP) and rheumatoid factor were also reduced in the HA-treated arthritic rats. Conclusion: The results of the present study demonstrate the anti-arthritic potential of HA leaves in the anti-arthritic activity. Keywords: Anti-arthritic, C-reactive protein, Complete Freud's adjuvant, Helianthus annuus, Paw volume, Rheumatoid factor.